Amelioration of streptozotocin-induced neurotoxicity in rats by a standardized extract of Cydonia oblonga seeds - Anwar, Rukhsana; Amna Gulzar, Dure e; Sattar, Ammara Abd us; Ashiq, Kanwal (Bangladesh Journal of Medical Science, 2022)
Background: Globally, medicinal plants are widely used to treat ailments due to their safety, accessibility and efficacy. Objectives: The objective of this study was to determine in vivo neuroprotective effect of methanolic extract of seeds of Cydonia oblongaagainst streptozotocininduced diabetes in rats, as this research has not been reported previously. Methods: Methanolic extract (100, 150 and 200 mg/kg b.w) was administered for 21 days to diabetic rats. Total protein content, glutathione-S-transferase (GST) specific activity, total glutathione level (tGSH), catalase activity (CAT), malondialdehyde (MDA) level, superoxide dismutase (SOD) level and acetylcholinesterase (AChE) activity were determined in the brain homogenate. Results: C. oblonga seeds extract showed a significantly (*p < 0.05) increased in GST activity, tGSH level, CAT activity and level of SOD. While MDA levels and AChE activity were decreased in comparison with streptozotocin-treated group. Histopathological examination also showed a marked improvement in the morphology of brain tissues. Conclusion: It is concluded that the methanolic extract of C. oblonga seeds has the potential to protect the brain against streptozotocin-induced neurotoxicity by reducing oxidative stress and is beneficial for cognitive improvement in diabetic patients. Bangladesh Journal of Medical Science Vol. 21 No. 04 October’22 Page : 848-857